PERANCANGAN SISTEM INFORMASI PRESENSI INTERN BERBASIS WEBSITE PADA BNI CORPORATE UNIVERSITY - Muhammad Fikri Alrasyid, (2023)
Attendance tracking is the process of recording someone's presence at an event, training, or activity they attended. Attendance tracking is important in various settings, including education, workplaces, and organizations. In an educational setting, class attendance is crucial for instructors to monitor student attendance, assign attendance grades, and take actions if students frequently miss or are late to class. In the workplace, attendance tracking is used to measure employees' punctuality, calculate salaries, and determine eligibility for bonuses or other incentives. Meanwhile, in organizations, attendance tracking at meetings or important events is used to ensure member attendance and participation, as well as to determine the number of attendees. Based on the interview with BNI Corporate University, it was found that there is a problem regarding the lack of an online attendance system for internal employees. In an effort to improve service quality and the efficiency of attendance management, BNI Corporate University requires a web-based attendance information system. The design and development of an attendance information system with attendance data for internal participants at BNI Corporate University would enable effective and efficient processing of attendance data.